Synthesis of a Nickel(I) alkoxide and related cation equivalents. (1st November 2021) - Dodd, Neil A.; Bacsa, John; Sadighi, Joseph P.
Graphical abstract: Protonolysis of a nickel(I) amide by neopentanol affords the corresponding alkoxide, which crystallizes as a paramagnetic dimer. Depending on stoichiometry, abstraction of alkoxide by a silyl triflate forms either a dinickel(I) complex bridged by one alkoxide and one triflate, or the monomeric nickel(I) triflate, crystallized as its diethyl ether adduct. Abstract: An ( N -heterocyclic carbene)nickel(I) hexamethyldisilazide deprotonates neopentanol (NpOH) to form the corresponding nickel(I) neopentoxide, which crystallizes as an alkoxide-bridged dimer. Reaction of the dimer with one equivalent of tert -butyldimethylsilyl trifluoromethanesulfonate gives an alkoxide-bridged dinickel(I) complex bridged by the CF3 SO3 (OTf) anion. In both [LNiONp]2 and [(LNi)2 (μ-ONp)(μ-OTf)], NiNi distances are consistent with the absence of metal–metal bonding, and Evans NMR data are consistent with the S  = 1 spin state. Treatment of the dimer with two equivalents of silyl triflate results instead in complete abstraction of alkoxide. Addition of diethyl ether forms the monomeric d 9 complex LNi(OEt2 )OTf.